2016
DOI: 10.1117/12.2218457
|View full text |Cite
|
Sign up to set email alerts
|

Acid generation efficiency: EUV photons versus photoelectrons

Abstract: EUV photoacid generation efficiency has been described primarily in terms of the EUV photon absorption by the PAG or the resist matrix and the production of low energy photoelectrons, which are reported as being ultimately responsible for the high quantum efficiencies reported in EUV resists (>1). Such observation led to a number of recent studies on PAGs with variable electron affinity (EA) and reduction potential (Ered) presumably conducive to a differential EUV photoelectron harvesting efficiency. However, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 43 publications
(44 reference statements)
2
23
0
Order By: Relevance
“…This high energetic barrier effectively "knocks out" the holeinduced chemistry pathway for the PMS resist, and yet acid is still produced, presumably entirely from the PAG. In addition, Thackeray et al [14], Goldfarb et al [18], and Tarutani et al [19] have shown that PAG reduction potential correlates well with EUV clearing dose, E 0 , and acid yield, indicating that PAG electron affinity directly relates to acid production in EUV exposure. Bulk electrolysis of PAGs at their reduction potentials has shown a 1:1 correlation between electrons injected and acid produced, demonstrating acid production through direct electron-PAG interactions at the low energies involved in electrolysis [9].…”
Section: Reaction Mechanisms In Chemically Amplified Resistsmentioning
confidence: 99%
See 1 more Smart Citation
“…This high energetic barrier effectively "knocks out" the holeinduced chemistry pathway for the PMS resist, and yet acid is still produced, presumably entirely from the PAG. In addition, Thackeray et al [14], Goldfarb et al [18], and Tarutani et al [19] have shown that PAG reduction potential correlates well with EUV clearing dose, E 0 , and acid yield, indicating that PAG electron affinity directly relates to acid production in EUV exposure. Bulk electrolysis of PAGs at their reduction potentials has shown a 1:1 correlation between electrons injected and acid produced, demonstrating acid production through direct electron-PAG interactions at the low energies involved in electrolysis [9].…”
Section: Reaction Mechanisms In Chemically Amplified Resistsmentioning
confidence: 99%
“…Researchers [2,3,6,8,10,[14][15][16][17][18][19] have proposed that the dominant chemical mechanisms involved in EUV chemically amplified resists include: (1) electron trapping (or dissociative electron attachment), (2) hole-initiated chemistry, or (3) internal excitation (or dissociative electron excitation), as described below ( Figure 6). In electron trapping, a low energy electron (perhaps 0-5 eV [17]) may be trapped by a PAG molecule, occupying an antibonding orbital in the PAG.…”
Section: Reaction Mechanisms In Chemically Amplified Resistsmentioning
confidence: 99%
“…It is unclear why the limit exists and why some PAGs have higher efficiency limits, but it may be related to the mechanism in which a PAG generates acid. There are three proposed mechanisms for an acid generation event when interacting with an EUV photoelectron: electron ionization (hole initiated chemistry), electron excitation (internal excitation) and electron attachment (electron trapping) [15,16]. Each mechanism will be affected to some extent by a few key factors such as the number and energy of electrons generated through an electron's energy loss cascade, the energy available to be deposited, and any polymer mediated effects.…”
Section: Concentration Effectsmentioning
confidence: 99%
“…then an increased likelihood for an electron-PAG interaction could explain the differing acid generation efficiencies. The reduction potential correlates to the electron affinity of a PAG, and other groups have shown that the tendency of a PAG to be reduced is related to the EUV photospeed such that a lower reduction potential usually results in a higher EUV photospeed [16,17]. Electrochemical PAG reduction experiments were conducted using a BASi Epsilon potentiostat with a Pt working electrode, Pt wire auxiliary electrode, and a Ag/AgCl reference electrode.…”
Section: Redox Potentialsmentioning
confidence: 99%
“…Experiments using electron energy loss spectroscopy (EELS) show evidence of internal excitation, 7,8 also known as electrical excitation 9 or dissociative electron excitation. 10 e-+ Previous work by Brainard 4,11 and Kozawa 6 ( Figure 2) indicates that chemically amplified resists can show maximum quantum yields of 5-6 acids produced per absorbed photon at very high PAG concentrations. Resists with higher quantum yield have lower Z-parameters, 12 so improving quantum yields should improve resist performance.…”
Section: Introductionmentioning
confidence: 96%